ANALISIS PENGARUH PENINGKATAN PASOKAN OKSIGEN PADA OPEN CATHODE PEMFC (PROTON EXCHANGE MEMBRANE FUEL CELL) DENGAN MENINGKATKAN KADAR OKSIGEN UNTUK MENCAPAI UNJUK KERJA FUEL CELL YANG OPTIMAL - Patrick Commanevendi; Waru Djuriatno; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
The performance of PEMFC is highly dependent on the level of oxygen supply to the cathode. The diffusion rate of oxygen through the cathode catalyst layer is influenced by factors such as the thickness and porosity of the layer, the oxygen concentration in the gas flow, as well as the temperature and pressure of the fuel cell. The level and quality of oxygen supply to the cathode play a crucial role in the fuel cell's performance. This research will discuss the analysis of the influence of increasing oxygen supply by increasing the oxygen content to the cathode and examine its effects on the performance of the Open Cathode PEMFC. This study utilizes a specialized system to support the measurement and reading of oxygen content values in the air using an oxygen sensor, as well as automation using a solenoid valve from a pure oxygen gas cylinder to achieve optimal oxygen content for the performance of the Open Cathode PEMFC. The research will be conducted by performing several experiments to increase the oxygen content in the vicinity of the fuel cell, which has been provided with a box-shaped space with a constant flow of hydrogen gas pressure into the fuel cell. Then, a hose will fill the space with pure oxygen gas mixed with ambient air from an air compressor to obtain the desired oxygen content value. The pressure of the oxygen gas and ambient air from this compressor is controlled by a solenoid valve. Subsequently, the voltage, current, and power output of the fuel cell will be measured from several experiments of increased oxygen content, which will be read using an oxygen sensor.